Exploring reflective practice among university English teachers in Yemen: A case study - Ahmed, Waleed Mohammed Abdullah (2014)
Reflection is an important teaching tool for teachers in higher education. By reflecting on the teaching performance, teachers can make sense of reflection for professional development and meaningful teaching and learning. Given that beliefs and practices are important components of reflective practice, more in-depth understanding of how teachers engage in reflection needs to be explored. Previous studies mainly focused on teacher‟s beliefs about reflection. However, little is known about how reflection is currently practiced among the university English teachers in Yemen. This study explores how reflection is practiced at one private university in Yemen by employing a qualitative case study method to gain insights into the phenomenon. Data were collected through a multipronged research approach including semi-structured interviews, semistructured classroom observations, journal entry and focus group discussions. Five teachers with ten-years of teaching experience were purposively selected as the key informants. Six to ten students taught by every informant took part in the focus group discussions. Data were analyzed using a coding scheme. The findings indicate that the teachers engaged in various levels, types and patterns of reflection. The multifaceted elements of reflection revealed that teachers‟ reflection was caused by two types of factors namely enabling and constraining factors. The study demonstrates that teachers need to constantly engage in formal, regular and collaborative reflection with students, colleagues, and administrators for professional development. The study provides several implications. Theoretically, the study leads to a critical awareness of the different layers of reflection. Practically, it gives teachers, administrators and decision-makers in-depth information about effective reflective practice, in particular, its process and relevance to teacher education. Methodologically, other studies can employ a similar approach to understand any complex phenomena related to teaching and learning. Further research studies are required to explore the roles of university administrators and policy makers in promoting effective reflection.